Benda Pusako Minangkabau sebagai Ide Penciptaan Lampu Hias dengan Teknik Ukir dan Kolase - Jiffi Machlan; Irwan Irwan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The aim of making this work is to visualize the application of Minangkabau pusako objects such as kurambik, keris, talempong, tingkuluak tanduak, tambua, carano, traditional clothing and other cultural tools into decorative objects, namely decorative lamps using carving and collage techniques. The creation method used in this final work is the exploration, design and embodiment stages to visualize Minangkabau pusako objects into decorative lamp works. Based on this method, works are created in the form of decorative lamps in various forms of Minangkabau pusako objects as objects, which are made using collage techniques. The author created seven works entitled (1) male kurambik decorative lamp (2) kurambik batano decorative lamp; (3) Carano decorative lamps with Ati Ati motifs; (4) Carano Kipeh Cino decorative lamps; (5) tingkuluak tanduak decorative lights; (6) Kapalo Buffalo Kaluak Paku decorative lights; (7) buffalo head decorative lamp.